2015
DOI: 10.1136/jnnp-2015-310972
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral adaptive deep brain stimulation is effective in Parkinson's disease

Abstract: Introduction & objectivesAdaptive deep brain stimulation (aDBS) uses feedback from brain signals to guide stimulation. A recent acute trial of unilateral aDBS showed that aDBS can lead to substantial improvements in contralateral hemibody Unified Parkinson’s Disease Rating Scale (UPDRS) motor scores and may be superior to conventional continuous DBS in Parkinson’s disease (PD). We test whether potential benefits are retained with bilateral aDBS and in the face of concurrent medication.MethodsWe applied bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
283
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(302 citation statements)
references
References 26 publications
3
283
1
1
Order By: Relevance
“…The source code, written in Python (Numpy,Scipy, Matplotlib), is freely distributed under the GPL License and can be found on-line at Github 3 . Figure 1 shows that the model reproduces sustained β-band oscillations in the absence of stimulation, as observed in the STN and GPe of parkinsonian patients (Little et al, 2016). At time t = 0.5 s the proportional feedback (4) is applied with gain k = 2.…”
Section: Parameters Choicementioning
confidence: 77%
See 1 more Smart Citation
“…The source code, written in Python (Numpy,Scipy, Matplotlib), is freely distributed under the GPL License and can be found on-line at Github 3 . Figure 1 shows that the model reproduces sustained β-band oscillations in the absence of stimulation, as observed in the STN and GPe of parkinsonian patients (Little et al, 2016). At time t = 0.5 s the proportional feedback (4) is applied with gain k = 2.…”
Section: Parameters Choicementioning
confidence: 77%
“…As reported in the survey paper (Carron et al, 2013), several attempts have been made in that direction. These include adaptive and on-demand stimulation (Rosin et al, 2011;Graupe et al, 2010;Santaniello et al, 2011;Little et al, 2016;Marceglia et al, 2007), delayed and multi-site stimulation (Lysyansky et al, 2011;Batista et al, 2010;Pfister and Tass, 2010;Tass et al, 2012), optimal control strategies (Feng et al, 2007), and activity regulation (Haidar et al, 2016;Wagenaar et al, 2005;Grant and Lowery, 2013).…”
Section: Problem Statementmentioning
confidence: 99%
“…This is to stimulate only when necessary and/or to adapt the strength of stimulation to the amount of abnormal neuronal synchrony. Initially introduced in computational studies with different types of specifically designed desynchronizing stimuli [61][62][63], demand-controlled DBS was experimentally tested by means of conventional high-frequency stimulation and denoted as adaptive DBS (aDBS) [64][65][66][67]. An alternative approach to significantly reduce stimulation current originated from computational studies on desynchronizing stimulation techniques [61][62][63]68] by incorporating spike timing-dependent plasticity (STDP) [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…Pulse width and frequency can also influence speech outcomes 47 48. Little et al 49 found adaptive DBS less detrimental to speech and maybe even capable of benefits.…”
Section: Language Changesmentioning
confidence: 99%